Imigrantes overclass: imigrantes empreendedores italianos no norte e nordeste brasileiro no começo do século XXI - Oliveira, André Luiz Santos de (2023)
The work consists of approaching cases of entrepreneurship carried out by immigrants of Italian origin installed in two capitals at the north and northeast of Brazil (Palmas - TO e São Luis – MA), that arrived in the country at the beginning of the 21st century. The method used is the Multiple Case Study in combination with the analytical model mixed embeddedness with adaptations. We seek to understand the processes of entry and the socioeconomic integration of immigrants. We investigated which relationships and networks are established or in which these immigrants are inserted and their importance in such processes; also, how the structure of opportunities is arranged in each of the cases, implying their transnational scope; The dynamics of capital mobilized in this process and the dispositions of nationals towards such immigrants are also explored and how they can be found reflected in the political-institutional apparatus and on the regulatory aspects that make up the reality of these immigrants in the studied locations. Literature`s perspective on the interaction between inequality, immigration and the role of policies and political regimes in this relationship have also served as contexts for the analyzes and discussions carried out on the cases. In this compass, we seek to verify: are the Italians in the studied locationsin the north and northeast of the country, in the studied time interval, to a certain extent, privileged as immigrants? or, are they overclass immigrants?